Kajian Mengenai Nilai Perolehan Objek Pajak Tidak Kena Pajak (NPOPTKP) Dalam Perda DKI Jakarta Nomor 1 Tahun 2024 Tentang Pajak Daerah Dan Retribusi Daerah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The tax on the acquisition of land and/or building rights is one of the largest sources of state revenue used to finance public needs, regulate economic activities, and promote equitable development within society. Thus, taxation plays a crucial role in the functioning of the state. This study examines and explores the imposition of the Non-Taxable Acquisition Value of Tax Object (NPOPTKP) as regulated in Jakarta Regional Regulation Number 1 of 2024 concerning Regional Taxes and Regional Levies, which affects the calculation of the Duty on the Acquisition of Land and/or Building Rights (BPHTB). This research employs a normative juridical method using secondary data as its primary source. The findings reveal the implementation, differences, and significant changes in the NPOPTKP provisions under Regional Regulation Number 1 of 2024 compared to the previous regulations.